İşe iade davalarının sonuçları - Avşar, Muhammed Emre (My University, 2018)
Tarihte hiçbir hakkı olmadan çalıştırılan işçiler, insanlığın ve hukukun gelişimi ile birlikte korunmaya ve çeşitli haklara sahip olmaya başlamışlardır. Süreç içerisinde iş güvencesi kurumu meydana gelmiş, iş ilişkisinin keyfi sona erdirilmesinin engellenmesi için bir dizi düzenlemeler yapılmıştır. İş hukukunun küresel boyutta gelişiminde en önemli nokta şüphesiz ILO’nun kurulması ve dünya devletleri tarafından ILO sözleşmelerinin kabul edilmesi olmuştur. ILO tarafından 158 sayılı Hizmet İlişkisine İşveren Tarafından Son Verilmesi Hakkında Sözleşmenin 1982 yılında kabul edilmesinden sonra iş güvencesi ve işe iade davaları, tüm dünyada olduğu gibi ülke hukukumuzda da yerini almıştır.Bu çalışmada ise, iş hukukunun en önemli ve güncel konularından olan “İşe İade Davaları”, sonuçları başta olmak üzere tüm yönleriyle incelenmiştir.Çalışmamız üç bölümden oluşmaktadır. İlk bölümde işe iade davalarının temelini oluşturan iş güvencesinin tanımı, şartları, hukuki ve tarihsel gelişimi ile iş sözleşmesinin feshi incelenmiş, ikinci bölümde feshe itiraz yani işe iade davası ele alınmış, üçüncü ve son bölümde ise işe iade davalarının sonuçları doktrin ve yargı kararları ışığında ele alınmıştır.

Workers, who have been employed without any right in the history, are started to be protected and have various rights with the development of mankind and the law. Within the process, the concept of labor-job protection has been established and a number of regulations have been introduced in order to prevent the arbitrary termination of the employment relationship. The most important point in the development of labor law on a global basis has undoubtedly been the establishment of the International Labor Organisation (‘ILO’) and the inclusion of ILO agreements into their domestic laws by world states. After the adoption of the Convention concerning Termination of Employment at the Initiative of the Employer (No. 158) in 1982, the labor-job protection and reinstatement lawsuits took place in our country as well as all over the world.In this study, “Reinstatement Lawsuits, which is one of the most important and current issues of labor law, has been examined in all its aspects, especially its results.This thesis consists of three parts. In the first part, the definition, conditions, legal and historical development of the labor-job protection which constitutes the basis of the reinstatement lawsuits and the termination of the employment contract were examined. In the second part, the termination appeal, namely reinstatement lawsuit was discussed and in the third and last part, the results of the reinstatement lawsuits were discussed in light of doctrine and judicial decisions.
Keywords: Arabuluculuk Returning to work; Geçersiz Fesih; Illegal Abolition; İş Güvencesi; İş hukuku; İşe İade; Job Security; Labor laws and legislation; Labour Law; Mediation